Teacher Development Program to Enhance the Effectiveness of Technology-Based Learning - Sabariah; Rufi’i; Suharyanto; Krisna Murti Anugraha; Robi’ati Fauziyah; Kadori; Supriyanto (Jurnal Edutech Undiksha, 2025)
In an era where rapid technological advancement affects all aspects, including education, there are still challenges in enhancing teachers' competence in technology. Many teachers continue to employ traditional methods without leveraging technology due to insufficient guidance. The implementation of ICT training often faces various challenges, such as teachers' ability to integrate technology into daily teaching practices is still lagging behind. Researchers examined the effectiveness of the Teacher Development Program to enhance technology-based learning at SD Negeri 1 Kedungpring through observation and interviews. It is anticipated that this program will positively impact the effectiveness of learning in the school. Based on the research findings, a significant number of teachers still use traditional teaching methods, with only 40% actively incorporating technology. Through development seminars and interviews, researchers found that this program effectively improves learning effectiveness. A majority of teachers stated that the development program has enhanced their competency in teaching with technology, resulting in positive impacts on student learning outcomes and overall instructional effectiveness.